Gut microbiota composition and phylogenetic analysis in autism spectrum disorder: a comparative study - Xiang, Fangtao; Zhang, Mei; Wei, Xin; Chang, Jiali (Frontiers in Psychiatry, 2025)
BackgroundAutism spectrum disorder (ASD) is frequently associated with gastrointestinal (GI) disturbances, implicating the gut microbiota and its metabolites, short-chain fatty acids (SCFAs), in disease pathology via the gut-brain axis. However, the microbial-SCFA nexus in ASD remains controversial, necessitating integrated analyses to clarify these relationships. This study aimed to investigate intestinal microbiota composition and its potential influence on SCFA production in children with ASD compared to typically developing Control, exploring links to GI symptoms and neurodevelopmental outcomes.MethodsFecal samples from 38 ASD children (aged 4–12 years) and 33 age-matched Control were analyzed using 16S rRNA gene sequencing (Illumina MiSeq, V3-V4 region) to assess microbial diversity, taxonomy, and predicted functions (PICRUSt2). Alpha and beta diversity, differential taxa, and metabolic pathways were evaluated with QIIME2, MetagenomeSeq, and LEfSe. SCFA production was inferred based on taxonomic composition and microbial abundance analysis.ResultsASD samples exhibited reduced alpha diversity (Chao1, Observed species, p < 0.05), distinct beta diversity (PERMANOVA, p = 0.001), and taxonomic shifts, with inferred Firmicutes depletion and Bacteroidetes enrichment. Predicted metabolic pathways suggested lower butyrate and higher acetate/propionate production in ASD (p < 0.01). Network analysis revealed diminished microbial connectivity, potentially disrupting SCFA synthesis.ConclusionsThese findings indicate microbial dysbiosis in ASD, likely skewing SCFA profiles toward reduced butyrate and elevated propionate, which may exacerbate GI and neurological symptoms. This supports microbiota-targeted interventions (e.g., probiotics) as potential therapeutic strategies, providing theoretical and data support for further determining the impact of SCFAs on metabolism.